Genocide and resistance Nr. 32(2) - Rukšėnas, Alfredas; Balbus , Tomasz; Noreika , Dainius; Banionis, Juozas; Grybkauskas, Saulius; Buchaveckas, Stanislovas (Genocidas ir rezistencija, 2012)
Full Issue